Rezūm for retention—retrospective review of water vaporization therapy in the management of urinary retention in men with benign prostatic hyperplasia. Issue 14 (20th July 2021) - Bassily, Daniel; Wong, Vincent; Phillips, John L; Fraiman, Mitchell; Bauer, Ross; Dixon, Christopher M; Wong, Nathan C
Abstract: Objective: Rezūm vapor ablation is a minimally invasive treatment for benign prostatic hyperplasia (BPH) that uses injections of sterile water vapor directly into the prostate for tissue ablation. Although Rezūm is currently indicated for use in men with prostate sizes ≥30 and ≤80 ml, it is unclear how effective Rezūm is for men in urinary retention. We sought to determine whether Rezūm is effective in the treatment of catheter‐dependent urinary retention secondary to BPH. Methods: A retrospective chart review was conducted on consecutive patients who presented for urinary retention and subsequently treated with Rezūm. We evaluated procedural details and examined variables pre‐ and post‐Rezūm (at 6 months) including International Prostate Symptom Score (IPSS), IPSS quality of life (IPSS–QOL), maximum flow (Qmax ), post void residual volume (PVR), prostate specific antigen, rate of retention, and use of alpha blockers and 5‐alpha reductase inhibitor (5ARI). Results: Of the 49 patients included in this study, median age of was 73 years, median prostate volume was 73cc (Interquartile range [IQR]: 50, 103) and a median lobe was present in 80% of patients. All patients were in urinary retention before treatment with a median PVR of 900 ml (IQR: 566, 1146). Following Rezum, IPSS (17 pre‐Rezūm, 4 post‐Rezūm) and IPSS–QOL (4 pre‐Rezūm, 1 post‐Rezūm) both improved at 6 months ( p < 0.01). Qmax increased from 3 to 6 ml/s ( p = 0.03) and PVR decreased from 900 to 78 ml ( p < 0.01). Only 17/38 patients taking alpha‐blockers and 7/15 patients on 5ARIs continued therapy at 6 months following Rezūm ( p < 0.01). Of the 49 patients treated, 10 (20.4%) remained in catheter dependent urinary retention following the procedure, and 6 remained in retention at 6 months (12.2%) even after further surgical therapies for BPH ( p < 0.01). Conclusion: Rezūm is a safe and effective therapy for treating catheter dependent urinary retention in patients with BPH, including those with median lobes. As a minimally invasive therapy, it is a promising option in patient, particularly those who are not suitable for prolonged anesthesia.